2020
DOI: 10.3390/app10030878
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost, Compact, and Rapid Bio-Impedance Spectrometer with Real-Time Bode and Nyquist Plots

Abstract: Bioelectric impedance spectroscopy (BIS) has been widely used to study the electrical properties of biological tissue based on the characteristics of the complex electrical impedance dispersions. One of the problems in using the BIS method is the length of time required for the data acquisition process and possibly data analysis as well. In this research, a compact and work rapidly BIS instrumentation system has been developed at a low cost. It is designed to work in the frequency range of 100 Hz to 100 kHz, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Work in compressive sensing has demonstrated that a sparse representation can be represented in a compressed form. In particular, in contrast to standard (Nyquist Santoso et al (2020)) sampling, compact sampling can produce a signal at a rate lower than Nyquist's criterion. The Min‐LL approach can be applied by solving a convex optimization problem called min‐LL with equality constraints.…”
Section: Machine Learning and Internet Of Thingsmentioning
confidence: 98%
“…Work in compressive sensing has demonstrated that a sparse representation can be represented in a compressed form. In particular, in contrast to standard (Nyquist Santoso et al (2020)) sampling, compact sampling can produce a signal at a rate lower than Nyquist's criterion. The Min‐LL approach can be applied by solving a convex optimization problem called min‐LL with equality constraints.…”
Section: Machine Learning and Internet Of Thingsmentioning
confidence: 98%
“…Complete blood cell counts were performed using an ABX Micros 60 Hematology Analyzer. Electrical impedance measurement was performed using BISDAQ [24]. The electrical impedance measurement is performed by injecting a current of 10 µA into a blood sample in the frequency range of 100 Hz -100 kHz.…”
Section: Electrical Impedance Spectroscopy Measurementsmentioning
confidence: 99%
“…However, the frequencies depend on the applicability of the bioimpedance analyzer, so may differ for skin moisture or ischemia level [31], specific cells detection [32,33], muscles assessment [34], and human body condition analysis [35][36][37]. In short, the different frequencies at which these devices excite the skin are summarized in Appendix A.…”
Section: Multisine Designmentioning
confidence: 99%